Therapeutic Potential of Neurotrophins for Repair After Brain Injury: A Helping Hand From Biomaterials - Houlton, Josh; Abumaria, Nashat; Hinkley, Simon F. R.; Clarkson, Andrew N. (Frontiers in Neuroscience, 2019)
Stroke remains the leading cause of long-term disability with limited options available to aid in recovery. Significant effort has been made to try and minimize neuronal damage following stroke with use of neuroprotective agents, however, these treatments have yet to show clinical efficacy. Regenerative interventions have since become of huge interest as they provide the potential to restore damaged neural tissue without being limited by a narrow therapeutic window. Neurotrophins, such as brain-derived neurotrophic factor (BDNF), and their high affinity receptors are actively produced throughout the brain and are involved in regulating neuronal activity and normal day-to-day function. Furthermore, neurotrophins are known to play a significant role in both protection and recovery of function following neurodegenerative diseases such as stroke and traumatic brain injury. Unfortunately, exogenous administration of these neurotrophins is limited by a lack of blood-brain-barrier (BBB) permeability, poor half-life and rapid degradation. Therefore, we have focused this review on approaches that provide a direct and sustained neurotrophic support using pharmacological therapies and mimetics, physical activity and potential drug delivery systems, including discussion around advantages and limitations for use of each of these systems. Finally, we discuss future directions of biomaterial drug-delivery systems, including the incorporation of heparan sulfate in conjunction with neurotrophin-based interventions.using pharmacological therapies and mimetics, physical activity and potential drug delivery systems, including discussion around advantages and limitations for use of each of these systems. Finally, we discuss future directions of biomaterial drug-delivery systems, including the incorporation of heparan sulfate in conjunction with neurotrophin-based interventions.